ANALISIS SIX SIGMA UNTUK PENINGKATAN KINERJA LAYANAN AKADEMIK SISWA DI SMK NEGERI 2 YOGYAKARTA - , Joko Prasetiyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to measure students academic service performance value in SMK Negeri 2 Yogyakarta service performance using instruments (servperf), and analyzed using six sigma to improve the academic performance of services. This research is a descriptive study, the population is 2,300 students of SMK Negeri 2 Yogyakarta school year 2012/2013, where as samples taken was 350 students. Quantitative data were obtained using instruments servperf given to 350 students with proporsionate stratified random sampling technique. The qualitative data obtained through interviews with teachers and administrators respondents SMK Negeri 2 Yogyakarta. Results of this study indicate that students level of satisfaction on the performance of academic services at servperf measurements are: 3.72 tangible dimension, reliability dimension 3.59, 3.53 dimensions of responsiveness, assurance dimension of 3.69, 3.38 empathy dimension. Average rating is 3.58, meaning that the overall academic performance of services in SMK Negeri 2 Yogyakarta at 71.64% and still provide opportunities for the emergence of dissatisfaction on the performance of such services students at 28.36%. Measurement results on measure phase, by these sigma level, the average performance achieved academic services SMK Negeri 2 Yogyakarta is 2.07 sigma level. According to the terminology of six sigma, companies or organizations that have a sigma level of 2.07 is classified as a company or organization that is not competitive. From interviews with teachers and the management of SMK Negeri 2 Yogyakarta then analyzed with the fishbone diagram, so we found the root cause of the problem and proposed solutions to improve the academic performance of services in terms of: (1) manpower (human resources), in this case is teachers and educational staff (teachers and employees), (2) machine, in this case the machinery and equipment as well as the supporting infrastructure of teaching and learning processes and practices, (3) methods , in this case include the methods and school management, and (4) materials.